lo g 2 x lo g 4 lo g 6 x = lo g 2 x lo g 4 x + lo g 4 x lo g 6 x + lo g 6 x lo g 2 x
Find the sum of real x satisfying the equation above..
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
lo g 2 x lo g 4 lo g 6 x lo g 2 lo g 4 lo g 6 lo g 3 x lo g 2 lo g 4 lo g 6 lo g 3 x lo g 3 x = lo g 2 x lo g 4 x + lo g 4 x lo g 6 x + lo g 6 x lo g 2 x = lo g 2 lo g 4 lo g 2 x + lo g 4 lo g 6 lo g 2 x + lo g 6 lo g 2 lo g 2 x = lo g 2 lo g 4 lo g 6 lo g 2 x ( lo g 2 + lo g 4 + lo g 6 ) = lo g 2 x lo g 4 8
⟹ lo g 2 x ( lo g x − lo g 2 4 ) = 0 ⟹ { lo g x = 0 lo g x − lo g 4 8 = 0 ⟹ x = 1 ⟹ x = 4 8 .
Therefore the sum of roots is 1 + 4 8 = 4 9 .
@Aly Ahmed , It is not \log 2^x lo g z x but \log 2 x lo g 2 x . I think this is the second time that I see this.
Problem Loading...
Note Loading...
Set Loading...
The given equation reduces to the form :
( ln x ) 3 = ( ln x ) 2 ( ln 2 + ln 4 + ln 6 )
⟹ ( ln x ) 2 ( ln x − ln 4 8 ) = 0
⟹ x 1 = 1 , x 2 = 4 8 , x 1 + x 2 = 4 9 .